Chemical Signals in Vertebrates 11 - Hurst, Jane.; Hurst, Jane.; Beynon, Robert J.; Beynon, Robert J.; Roberts, S. Craig.; Roberts, S. Craig.; Wyatt, Tristram.; Wyatt, Tristram. (Springer New York : Imprint: Springer, 2008)
This volume presents the proceedings of "Chemical Signals in Vertebrates 11", hosted by the University of Liverpool and held July 25 - 28, 2006 at the University of Chester in the United Kingdom. Chemical Signals in Vertebrates 11 contains the latest research on chemical communication relevant to vertebrates, particularly focusing on new research since the last meeting in 2003. Topics covered include chemical ecology, biochemistry, behavior and neurobiology of both the main olfactory and vomeronasal systems of vertebrates, from amphibia to mammals including humans. A broad range of taxonomic groups and topics are discussed, including sections on new directions in semiochemistry, olfactory response and function, recognition within species, sexual communication, maternal-offspring communication, communication between species, and applications for zoo animal enrichment and pest control. The volume is dedicated to the memory of Dr. Bets Rasmussen and includes a special tribute chapter on her ground-breaking research on elephant communication. About the Editors: Dr. Jane L. Hurst is a Professor in the Faculty of Veterinary Science at the University of Liverpool, Liverpool, UK, where she heads the Mammalian Behaviour and Evolution Research Group. Dr. Rob Beynon is also a Professor in the Faculty of Veterinary Science at the University of Liverpool, Liverpool, UK where he heads the Proteomics and Functional Genomics Research Group. Dr. S. Craig Roberts is a Lecturer in the School of Biological Sciences at the University of Liverpool, Liverpool, UK where he is a member of the Evolutionary Psychology Research Group. Dr. Tristram Wyatt is the Director of Distance and Online Learning at the University of Oxford, Oxford, UK and also a research associate at the Department of Zoology.